Super-twisting Sliding Mode Control of a Doubly-fed Induction Generator Based on the SVM Strategy - Yaichi, Ibrahim; Semmah, Abdelhafid; Wira, Patrice; Djeriri, Youcef (Periodica polytechnica. Electrical engineering and computer science, 2019)
This paper presents direct power control (DPC) strategies using the super-twisting sliding mode control (STSMC) applied to active and reactive power control of a doubly-fed induction generator (DFIG) supplied by a space vector modulation inverter for wind turbine system. Then, a control STSMC-DPC and SVM strategies are applied. The active and reactive powers that are generated by the DFIG will be decoupled by the orientation of the stator flux and controlled by super-twisting sliding mode control. Its simulated performance is then compared with conventional sliding mode control. The test of robustness of the controllers against machine parameters uncertainty will be tackled, and the simulations will be presented. Simulation results of the proposed controller (SMC-DPC) and (STSMC-DPC) scheme are compared for various step changes in the active and reactive power. This approach super-twisting sliding mode control is validated using the Matlab/Simulink software and the results of the simulation can prove the excellent performance of this control in terms of improving the quality of the energy supplied to the electricity grid.